PENGARUH MOTIVASI KERJA, KOMPENSASI, KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA TEKNISI PADA PT TRI CAHAYA TEKNIK BANDAR LAMPUNG - Luthfia Ardana; Iskandar Ali Alam (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aims to analyze the impact of work motivation, compensation, and Occupational Safety and Health (K3) on technician performance at PT Tri Cahaya Teknik Bandar Lampung. Using an associative quantitative method, data were collected through questionnaires from 36 technicians as research samples. Data analysis techniques used include multiple linear regression, t-test, and F-test. The test results show that work motivation and compensation have a partial significant effect on performance. In contrast, the K3 variable does not have a significant effect independently on technician performance at this company. Collectively, the three variables have a positive effect with a contribution of 77.6% on technician performance.